Data migration strategy of heterogeneous systems / Noor Syafiqah Ab Manah - Ab Manah, Noor Syafiqah (2016)
Data Migration has become main project highlight in information technology and computing field for years now. Many companies and organization has benefited from data migration, to make money out of it by selling tools and infrastructure for data migration processes. Note that data migration project required large amount of funding to be carried out, issues and risk of data migration cannot be delivered up to expectation may be a nightmare to the related organization or client. Without correct and suitable data migration strategy, many data migration projects has failed, go over budget or delivered late. This research is hoped to weight out industrial concern on failed data migration project by proposing the Data Migration Strategy of Heterogeneous System. Context of the Data migration project for this research is moving multiple data sources including legacy system, existing system and application into a single target system or platform. This research is hoped to benefit society especially the organization that will go through data migration project of the same scope with this research.